Bridging the gap: how to adopt opportunistic plant observations for phenology monitoring - Katal, Negin; Rzanny, Michael; Mäder, Patrick; Römermann, Christine; Wittich, Hans Christian; Boho, David; Musavi, Talie; Wäldchen, Jana (Frontiers in Plant Science, 2023)
Plant phenology, which examines the timing of recurring life cycle events such as the onset of flowering, plays a vital role in assessing climate change. To ensure accurate predictions, extensive efforts are underway to monitor and anticipate changes in phenological events.Traditionally, individual plants are directly visited and observed by trained volunteers organized in national or international networks. However, the decreasing number of observers poses a significant threat to the reliability of predictions. In this study, we explore the feasibility of using plant observations captured opportunistically through AI-based plant identification apps to determine the onset of flowering. These observations are compared to data collected by dedicated phenological observers who specifically recorded these flowering events. With this, we introduce a supplementary approach that incorporates opportunistic plant observations into existing phenology monitoring systems. Our results show that for frequently observed, herbaceous and conspicious species, the patterns of onset of flowering were similar and comparable between both data sources. We argue that a prominent flowering stage is crucial for accurately determining the onset of flowering from opportunistic plant observations, and we discuss additional factors contributing to the differences among species. In conclusion, our study demonstrates that the phenological monitoring of certain species can benefit from incorporating opportunistic plant observations. Furthermore, we highlight the potential to expand the taxonomic range of monitored species for phenological stage assessment through opportunistic plant observation data.